When pancreas solid mass meets liver cystic lesion: A case report. Issue 1 (11th March 2021) - Han, Haifeng; Yang, Jian; Hu, Sanyuan; Zhan, Hanxiang
Abstract : Abstract: Pancreatic neuroendocrine tumors are in low incidence compared with other pancreatic tumors, and they present as various pathological forms, including solid, cystic and solid-cystic lesions. Herein, we report a rare case that presents cystic lesions in liver originating from solid pancreatic neuroendocrine tumors. It can be easily misdiagnosed pancreatic ductal adenocarcinoma or primary hepatic cancer according to imaging by surgeons without extensive professional experience. Therefore, it reminders surgeons the privotal role of pathological biopsy to diagnose the disease correctly. The ethical approval and written consent were waived by the institutional review board of our hospital owing to the retrospective nature of the study and routine treatments performed on this patient in clinical practice.